PONDOK PESANTREN MUKMIN MANDIRI AND ITS ROLE ON THE COMMUNITY DEVELOPMENT IN THE FRAMEWORK OF MAQASHID SHARIAH - Achmad Rifkih Mansur; Tika Widiastuti (Universitas Airlangga, 2020)
This study aims to determine the role of the Pondok pesantren Mukmin Mandiri towards the community within the maqashid syariah framework. The research method used is a descriptive qualitative approach. The data used in this study are primary data obtained from the Pondok pesantren Mukmin Mandiri Sidoarjo and the community around the pesantren. This study revealed that pesantren have the potential to develop an Islamic perspective. The focus of economic development does not lie in mere material development. Still, it must place man as his main subject and object in relation to the Khalifah of Allah on Earth. This study uses maqashid syariah as a fundamental theory. Classifying the activities of the pesantren Mukmin Mandiri activities into the sharia maqashid dimensions, namely religion (din), soul (nafs), reason (aqal), descent (nasl) and treasure (maal). The results showed that pesantren have a role in community development in terms of Islamic development based on maqashid syariahKeywords: Community Development, Islamic development, Maqashid syariah and Pondok PesantrenREFFERENCE Ausaf Ahmad. (1998). Economic development in islamic development revisited, dalam Development and Islam: Islamic perspectives on Islamic development. New Delhi: Institute of Objective Studies.Chapra, Umar. (2000). Islam dan pembangunan ekonomi, edisi terjemahan. Jakarta: Gema Insani.Chapra, Umar. (2008). The Islamic vision of development in the light of maqashid al shariah. Jeddah: Islamic Research and Training Institute.Jamaluddin, Muhammad. (2012). Metamorfosis Pesantren di Era Globalisasi. Jurnal Karsa, 20(1), 127-139.Nadzir, Mohammad. (2015). Membangun pemberdayaan ekonomi di pesantren. Jurnal Economica, 6(1), 37-56Nafi’,M. D., dkk. (2007). Praksis pembelajaran pesantren. Yogyakarta: Institute for Training and Development Amherst MA.P3EI. (2012). Ekonomi Islam. Jakarta: PT. RajaGrafindoPersada.Saifullah. (2012). Ekonomi pembangunan Islam. Bandung: Gunungdjati Press.